Transformation of Artificial Intelligence (AI) Based Credit Risk Assessment in Sharia P2P Lending: Perspectives Economic Law and Positive Law of Indonesia - Masir Rambe; Syilvia Kurnia Ritonga (Yurisprudentia: Jurnal Hukum Ekonomi, 2026)
This study aims to analyze the transformation of the use of Artificial Intelligence (AI) in credit risk assessment on the Sharia Lending Peer-to-Peer (P2P) platform and examine its conformity with the principles of sharia economic law and positive legal regulations in Indonesia. The use of AI is able to increase the speed, accuracy, and efficiency of the credit analysis process, but at the same time raises normative issues related to the validity of digital contracts, algorithm transparency, organizer accountability, personal data protection, and compliance with the principles of justice (al-'adl), trust, and benefits (maslahah). This research uses normative legal methods with legislative, conceptual, and philosophical approaches. Primary legal materials include DSN-MUI Fatwa Number 117/DSN-MUI/II/2018, POJK Number 10/POJK.05/2022, and Law Number 27 of 2022 concerning Personal Data Protection. The results of the study show that AI can be applied in Sharia P2P Lending as an instrument (wasilah) that is justified as long as its use supports the achievement of sharia goals (maqashid al-shari'ah) and does not contain elements of tyranny, gharar, or discrimination. However, AI characters that are black boxes have the potential to cause algorithmic bias, low transparency, and unclear legal accountability. On the other hand, national regulations have not regulated algorithm transparency standards or AI-based sharia supervision mechanisms comprehensively. Therefore, an integrative regulatory model is needed that synergizes sharia principles, AI ethics, and national law to realize legal certainty, substantive justice, and the sustainability of the sharia fintech ecosystem in the digital era.